2012
DOI: 10.1210/me.2011-1382
|View full text |Cite
|
Sign up to set email alerts
|

Research Resource: Diagnostic and Therapeutic Potential of Nuclear Receptor Expression in Lung Cancer

Abstract: Lung cancer is the leading cause of cancer-related death. Despite a number of studies that have provided prognostic biomarkers for lung cancer, a paucity of reliable markers and therapeutic targets exist to diagnose and treat this aggressive disease. In this study we investigated the potential of nuclear receptors (NRs), many of which are well-established drug targets, as therapeutic markers in lung cancer. Using quantitative real-time PCR, we analyzed the expression of the 48 members of the NR superfamily in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…To test this hypothesis, we analyzed the effects of pioglitazone treatment on cell cycle progression and the levels of reactive oxygen species in the lung cancer cell lines. Using DNA content analysis by FACS we found that pioglitazone treatment caused G1 arrest in both NCI-H2347 and NCI-H1993 cells (Figures 3A and 3B) but not in NCI-H1299 and NCI-H1395 cells (Figures S1A and S1B) that are essentially PPARγ-negative (Jeong et al, 2012). The pioglitazone-induced cell cycle arrest coincided with a marked reduction in the levels of phosphorylated RB in the NCI-H2347 and NCI-H1993 cells within 24 hours of treatment (Figure 3C), but not in the PPARγ-negative NCI-H1299 and NCI-H1395 cells (Figure S1C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To test this hypothesis, we analyzed the effects of pioglitazone treatment on cell cycle progression and the levels of reactive oxygen species in the lung cancer cell lines. Using DNA content analysis by FACS we found that pioglitazone treatment caused G1 arrest in both NCI-H2347 and NCI-H1993 cells (Figures 3A and 3B) but not in NCI-H1299 and NCI-H1395 cells (Figures S1A and S1B) that are essentially PPARγ-negative (Jeong et al, 2012). The pioglitazone-induced cell cycle arrest coincided with a marked reduction in the levels of phosphorylated RB in the NCI-H2347 and NCI-H1993 cells within 24 hours of treatment (Figure 3C), but not in the PPARγ-negative NCI-H1299 and NCI-H1395 cells (Figure S1C).…”
Section: Resultsmentioning
confidence: 99%
“…For the cistrome analysis, we used chromatin immunoprecipitation followed by deep sequencing (ChIP-seq) with NCI-H2347 and NCI-H1993 lung adenocarcinoma cells, which express PPARγ at high levels and whose growth is inhibited by TZDs such as pioglitazone and troglitazone (Jeong et al, 2012). We found 2225 regions in NCI-H2347 cells and 1419 in NCI-H1993 cells with a significantly increased occupancy for PPARγ (Figure 1A, Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many investigations are now aimed at determining whether PPARc and its ligands could be used as therapeutics for cancer treatment. Jeong et al showed that PPARc-positive lung cancer cell lines are more sensitive to the anti-cancerous effects of its ligands, implicating its possible usage for cancer therapy (Jeong et al 2012). In a phase 2 clinical trial, troglitazone showed that it could inhibit the growth of prostate cancer cells .…”
Section: Pparc As a Therapeutic Targetmentioning
confidence: 99%